Ophthalmology: Current and Future Developments: Volume 3 - Diagnostic Atlas of Retinal Diseases - Soriano, Mitzy E. Torres; Aguirre, Gerardo García; Gordon, Maximiliano; Graversen, Veronica Kon (Ophthalmology: Current and Future Developments, 2017)
This 3 volume set offers a comprehensive compilation which presents detailed information about ophthalmic (retinal, vitreous and macular) diseases. Key features of this set include: Emphasis on practical features of clinical diagnosis Concise and didactic presentation of key manifestations of diseases designed for rapid reference and target recall A vast selection of illustrations to sharpen clinical problem-solving skills Step by step treatment approaches to enhance the reader's ability to handle medical cases Citations or relevant research articles in each chapter for further reading The third volume of this set covers eye infections (bacterial and viral), inflammatory disorders and neoplasms. Written by a group of retina specialists, this book is an excellent resource for knowledge about retinal disorders. The streamlined format and evidence based medicine presented in the volume make this book the perfect reference for medical students, residents, general ophthalmologists and retina specialists.